Dual Sensory Loss and Depressive Symptoms: The Importance of Hearing, Daily Functioning, and Activity Engagement - Kiely, Kim M.; Anstey, Kaarin J.; Luszcz, Mary A. (Frontiers in Human Neuroscience, 2013)
Background: The association between dual sensory loss (DSL) and mental health has been well established. However, most studies have relied on self-report data and lacked measures that would enable researchers to examine causal pathways between DSL and depression. This study seeks to extend this research by examining the effects of DSL on mental health, and identify factors that explain the longitudinal associations between sensory loss and depressive symptoms. Methods: Piecewise linear-mixed models were used to analyse 16-years of longitudinal data collected on up to five occasions from 1611 adults (51% men) aged between 65 and 103 years. Depressive symptoms were assessed by the Centre for Epidemiological Studies Depression (CES-D). Vision loss (VL) was defined by corrected visual acuity greater than 0.3 logMAR in the better eye, blindness or glaucoma. Hearing loss (HL) was defined by pure tone average (PTA) greater than 25 dB in the better hearing ear. Analyses were adjusted for socio-demographics, medical conditions, lifestyle behaviours, Activities of Daily Living (ADLs), cognitive function, and social engagement. Results: Unadjusted models indicated that higher levels of depressive symptoms were associated with HL (B=1.16, SE=0.33) and DSL (B=2.15, SE=0.39) but not VL. Greater rates of change in depressive symptoms were also evident after the onset of HL (B=0.16, SE=0.06, p